Dynamics of vantovy avtodorozhny bridge - G. M. Kadisov (Вестник СибАДИ, 2017)
The task about fluctuations of the cable-stayed bridge presented by a fold with absolutely rigid cross diaphragms, a pole and guys together with a regular column of the trucks moving with a constant speed is investigated by the numerical decision of system of the integrated equations of Voltaire of the first sort. On a concrete example possibility of a resonance at the movement of a column with a speed equal to the regularity step relation to the period of own form of the bridge is shown, taking into account frequency-dependent internal friction.